Factors affecting firm's financial performance: a study on the selected listed companies in Malaysia / Muhammad Fakrul Razhi Mohd Zaidi - Mohd Zaidi, Muhammad Fakrul Razhi (2021)
Firm's financial performance is an important part for the company. The financial performance issues had been discussed among nations and organizations leaders throughout the world. Board of directors are expected to play an important role in ensuring the stability of the company's financial performance. The purpose of conducting this study is to determine which variables could be the factors affecting the firm's financial performance in Malaysia. This study will use financial performance as dependent variable and board size, leverage and firm size as independent variable. The observations for this study consist of 30 listed companies in Malaysia that have been selected with time period consists of five years which is from 2015 to 2019. These data were collected from Refinitiv Eikon by Thompson Reuters. In the past studies, several researchers have been conducted their research that related with this study and from their study shows several result that there is positive relationship between dependent variable with independent variables and several result shows that there is negative relationship between dependent variable and independent variables.